Practical multivariate analysis - Afifi, A. A. (Abdelmonem A.), 1939-; May, Susanne; Clark, Virginia, 1928-; Afifi, A. A. (Abdelmonem A.), 1939- (Boca Raton : Taylor & Francis, 2012)
The book contains information on how to perform multivariate statistical analysis and how to understand the results using the most recent software versions. It also discussed the most modern ways of performing the circulation.
Rev. ed. of: Computer-aided multivariate analysis. 4th ed. c2004.
Includes bibliographical references and index.
opc 29/04/13
Loans
Keywords: Multivariate analysis -- Data processing